Impact of health shocks on household consumption structure - Qiu, Yinxin; Zhang, Fen (Frontiers in Public Health, 2024)
In light of the recent pandemic, the impact of health shocks on household consumption patterns warrants further attention. Medical expenses have become a significant focus in the transformation of China's household consumption structures. Data was sourced from the China Family Panel Studies (2010-2018, 5 waves), encompassing a total of 25,809 participants. Utilizing the health deficit theory by Dalgaard and Strulik (2014), our paper constructed an empirical model and conducted regression analysis to investigate the impact of health shocks on household consumption patterns. Health shocks were measured using the logarithmic value of the difference between actual and predicted medical expenditures, termed stochastic medical expenditure. The analysis revealed that health shocks significantly increased the proportion of household spending on medical expenses. Consequently, expenditures on food and education experienced varying degrees of reduction as households adjusted their budgets to cope with health shocks. Notably, households with lower incomes and those without health insurance were particularly affected. Our findings indicate that health shocks adversely impact the structure of household consumption. We recommend that the government promote improvements in residents' health, reduce the financial burden of medical expenses, and explore the potential for increased consumption. Additionally, it is crucial to prioritize economic growth and implement systematic measures to mitigate health shocks and effectively enhance household consumption patterns.